의료소비자의 특성별 치과의료기관 선택기준에 관한 분석 - 배미란(Mi-Ran Bae); 전진호(Jin-Ho Chun); 이정화(Jung-Hwa lee) (한국콘텐츠학회 논문지, 13(3), 2013)
The subjects of this study were the patients of H Dental Hospital in Busan, who visited for the purpose of treatment in patients over 18 years of age and 151 patients, analyzed the data of the results of the selection criteria of the dental health care consumer. The gender of the subjects by cross-analysis, importance order of selection criteria for dental hospital were cleanness and hygiene(78.1%), equipment and facilities(60.9%), career and word-of-mouth(57.6%), staff kindness(57.6%), ease of use(32.5%) and scale of dental hospital(22.5%), it was appeared similar in comparison of cross-analysis and average-analysis. Major consideration of the study subjects to select criteria for dental hospital was pain control(31.8%), infection control(30.5%), cost(29.8%), time(7.9%) respectively. Gender as a primary consideration to the part of a man in pain control(39.2%), women cost(39.1%) was most common (p<0.001). In dental health care consumer to select criteria, clean hygiene and infection control at the heavily appeared to affect the direction of change in the consciousness of consumers seeking and it is necessary to improve hospital services for the dental care of their qualitative changes. 본 연구에서는 부산지역 H치과병원에 내원하고 있는 18세 이상의 환자 151명을 대상으로 자료를 분석하여 의료소비자의 치과진료기관 선택기준을 살펴봄으로써 향후 병원경영 및 이미지 향상에 기초자료로 제공하고자 하였다. 연구대상자의 성별 의료기관 선택 기준별 중요도 교차분석에서 청결위생(78.1%), 시설장비(60.9%), 경력입소문(57.6%), 의료진 친절(57.6%), 이용 편리성(32.5%), 기관 규모(22.5%)의 순으로 나타났고, 평균비교에서도 청결위생, 진료진 친절, 시설, 장비, 경력, 입소문 순으로 교차분석과 비슷하게 나타났으며, 연구대상자가 의료기관 선택 시 최우선적으로 고려하는 부분은 통증처치(31.8%), 감염관리(30.5%), 진료비(29.8%), 진료시간(7.9%)의 순이었다. 성별로 최우선적으로 고려하는 부분은 남자는 통증처치(39.2%), 여자는 진료비(39.1%)가 가장 많았다(p<0.001). 의료소비자의 치과의료기관 선택 시 청결위생상태 및 감염관리를 비중있게 생각하는 것으로 나타나 의료소비자의 의료기관 재 이용의사에도 어느 정도 영향을 주고 있으므로 이에 부응하기 위해 의료소비자를 만족시킬 수 있는 치과의료진의 청결위생과 감염관리의 인식과 실천이 필요할 것으로 사료된다.